2022
DOI: 10.1038/s42003-021-02992-4
|View full text |Cite
|
Sign up to set email alerts
|

The metabolic stress-activated checkpoint LKB1-MARK3 axis acts as a tumor suppressor in high-grade serous ovarian carcinoma

Abstract: High-grade serous ovarian carcinoma (HGSOC) is the most aggressive gynecological malignancy, resulting in approximately 70% of ovarian cancer deaths. However, it is still unclear how genetic dysregulations and biological processes generate the malignant subtype of HGSOC. Here we show that expression levels of microtubule affinity-regulating kinase 3 (MARK3) are downregulated in HGSOC, and that its downregulation significantly correlates with poor prognosis in HGSOC patients. MARK3 overexpression suppresses cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 51 publications
0
19
2
Order By: Relevance
“…Similarly, when MARK3 knockout is combined with GGTI-298, the effect on transcription of YAP1/TAZ target genes is significantly enhanced, and the growth of some MARK3 KO UM cell lines is synergistically inhibited. However, the synergistic effect of the combination is not expression significantly correlated with poor prognosis in HGSOC patients [39]. This report is in contrast with our finding that high levels of MARK3 correlates with worse prognosis of UM patients and that higher MARK3 expression correlated with monosomy of chromosome 3.…”
Section: Discussioncontrasting
confidence: 99%
“…Similarly, when MARK3 knockout is combined with GGTI-298, the effect on transcription of YAP1/TAZ target genes is significantly enhanced, and the growth of some MARK3 KO UM cell lines is synergistically inhibited. However, the synergistic effect of the combination is not expression significantly correlated with poor prognosis in HGSOC patients [39]. This report is in contrast with our finding that high levels of MARK3 correlates with worse prognosis of UM patients and that higher MARK3 expression correlated with monosomy of chromosome 3.…”
Section: Discussioncontrasting
confidence: 99%
“…While prior studies have identified functions for specific MARK kinases in cancer (32)(33)(34), the essential redundant function of MARK2/3 in human cancer cells has, to our knowledge, not been previously defined.…”
Section: Resultsmentioning
confidence: 91%
“…After 48 h, cells were washed with ice-cold PBS (−), and total RNA was extracted using QIAzol Lysis Reagent and RNeasy Plus Mini Kit (Qiagen; 73404), according to the manufacturer’s instructions. The subsequent steps have been previously described [ 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…Bioinformatic analysis of RNA-seq and ChIP-seq experiments were previously described [ 30 , 31 ]. Gene Ontology and pathway analyses were performed using the clusterProfiler R package (v3.14.3) and visualized using Cytoscape (v3.6.1) with plug-in (ClueGOv2.5.1) [ 32 , 33 , 34 ].…”
Section: Methodsmentioning
confidence: 99%